Report on the 15th Annual Meeting of the Hannah Arendt Circle - Benjamin, Lucy; Brickacek, Katherine (HannahArendt.net, 2022)
The 15th Annual Meeting of the Hannah Arendt Circle was hosted by Loyola University Chicago on March 16-18, 2022. After a two-year pandemic-imposed postponement of the 14th Circle, we happily convened this year in a hybrid setting. The meeting was organised by Lucy Benjamin (University of Melbourne), Katherine Brichacek (Northwestern University), and Jennifer Gaffney (Loyola University Chicago). We are especially grateful to Loyola’s Philosophy Department for their enthusiastic support.